A systematic review of studies involving canopy layer urban heat island: Monitoring and associated factors - Yuanzheng Li; Tengbo Yang; Guosong Zhao; Chaoqun Ma; Yan Yan; Yanan Xu; Liangliang Wang; Lan Wang (Ecological Indicators, 2024)
The urban thermal environment is closely related to the well-being of many city dwellers. Rich achievements have been obtained for canopy layer urban heat island (CLUHI) studies. Nevertheless, the monitoring and associated factors of CLUHI have not been systematically and timely reviewed. Therefore, this paper aimed to solve this issue to some extent by reviewing the fruitful research progress of CLUHI from the above-mentioned two aspects. The main findings were as follows. (1) Eight methods were adopted to obtain near-surface temperature data for CLUHI research, including four observation, two numerical modeling, remote sensing and data assimilation methods. (2) Air temperature was usually used rather than apparent temperature indices. Obvious differences existed between them, especially under humid hot or cold windy conditions. (3) The CLUHI intensity was generally defined as the differences in temperature between urban and suburban or rural stations or regions by population, land cover/land use, etc, or derived using regression analysis between temperature and impervious surface percentage. (4) The diurnal, monthly, seasonal or interannual variation of CLUHI has been generally analyzed in various global regions. (5) Six types of factors were analyzed, including meteorological conditions, air pollution, socioeconomic factors, urban underlying surface condition, inland or coastal type and landform conditions, and combined effects of some factors. (6) Five potential research directions were proposed, including improvement of data acquisition, sharing and use, considering apparent thermal indices, focus on the rarely studied regions, cities and scales, improving the calculation of CLUHI intensity, and attention to more associated factors and driving force analysis methods. This review can provide references for future CLUHI research and the construction of climate-resilient, livable, low-carbon cities.